IMPLEMENTASI PEMIKIRAN EMMANUEL LEVINAS DALAM TEORI TANGGUNG JAWAB TERHADAP ORANG LAIN DAN RELEVANSINYA BAGI RELASI ANTAR MANUSIA PASCA COVID-19 - Ngatun; Adry Yanto Saputra (Aggiornamento, 2020)
The focus of my writing on Emmanuel Levinas's thoughts on the theory of responsibility towards others. The purpose of this paper is to explore how much influence Levinas' thoughts have on human relations in reading Covid 19. The author uses the literature method to work on this article. The author explores books and articles in scientific journals that have something to do with the theme the author adopts. The author found that Levinas's thoughts on the theory of responsibility towards others are very contextual in relation to human relations after the COVID-19 pandemic.